Technical analysis : a study on the feasibility of using the technical indicators RSI, MACD and the Livermore Market Key on liquid stocks in the Singapore market - Lai, Weilun (2008)
The present research study aims to ascertain the feasibility of using certain technical indicators in the context of the Singapore stock market. The paper looks into the trend indicator, Moving Average Convergence Divergence (MACD); the momentum based oscillator, Relative Strength Index (RSI), and the proprietary market timing technique developed by Jesse Livermore, the Livermore Market Key.